MAGNETIC-PULSE PRESSING OF ELECTRICAL CONNECTIONS FOR STRANDED WIRES - Zh. V. Samokhvalova (Електротехніка і електромеханіка, 2019)
Purpose. The research of the process peculiarities of magnetic- pulse fitting of electric stranded conductor joints, made of different materials, using couplings. Evaluation of loading optimal parameters, providing high operational reliability of electric connecting units. Methodology. In order to carry out simulation and research of the process of magnetic-pulse fitting of electric stranded conductor joints CRUG24 software package was used, which was developed to estimate impact interaction. Handling the problem was carried out numerically using finite differences. Metallographic study of collected cross-sectional cuts was performed with the use of optical microscope МЕТАМ ЛВ-71, equipped with digital-still camera, connected to the computer, which used image analysis system IMEGE Expert Pro3. The electrical tests of wire joints were carried out using the thermal bench from exposure to two factors: heating with rated current and expansion by operating load. Results. It was ascertained that magnetic-pulse pressing of electric joints was followed by partial self-purification and bedding component contacting surfaces of electric joints. Oxides and contaminating impurities were expelled into small localized zones between wires, between a wire and a coupling, which resulted in the contact of juvenile surfaces. Upon mutual deformation and displacement of metal wire surface capacity size and coupling tight mechanical contact was created, which provided minimal transient resistivity. The existence of residual compression stress provides the longstanding high-quality electric contact in joints. While using magnetic-pulse pressing of electric joints, due to high speed of deformation and impact of great inertial forces, deformation containment of connected components takes place in the zone of load action. The wires in contact with each other and with couplings generate faceting, but coupling sidewall hardly has any thinning. Filled density of cross-section is approximately 100 %. This fact provides a high degree of sealing capacity of joints, which to a wide extent prevents the oxidation of contacting surfaces and the rise of transient resistivity of electric joints in the operational process. As a result of processing of the results of thermal and electrical tests it was ascertained that pressed joint factors of defectiveness with all types of wires according to thermal impact and resistivity, are significantly lower than unity. Practical value. Magnetic-pulse pressing of unattended joints in electric stranded monometallic, bimetallic and composite conductors provides high operational reliability of connecting units and it may be used while mounting overhead system of railways, transmission lines and fitting connecting components of electrical transport electric circuits.